Developing Mediterranean and Western Diets for an Anti-Inflammatory Feeding Trial (P12-017-19). (13th June 2019) - Schweitzer, Amy; Barron, Bobbie; Barron, Nga; McCormack, Meredith; Brigham, Emily
Abstract: Objectives: Design a research diet that can be used to evaluate the relationship between nutrition and inflammation in a randomized, cross-over study in adults. Methods: Dietary components were established for a Mediterranean menu and a Western menu based on a literature review. Three-day menu cycles were planned using the established components. Recipes were developed and adapted to meet menu goals at the 2000 calorie level. Proportional increments of menu items at the 2000 kcal level were used to establish 2500, 3000, and 3500 daily kcal levels to allow for varying energy requirements of participants. Meal plans were analyzed using Nutrition Data System for Research 2017 (NDSR). Healthy Eating Index was calculated using NDSR data. Results: 100% of grains in the Mediterranean diet, none in the Western diet, were whole grains. Sweets and pastries were included in the Western diet daily but not the Intervention diet. Mean HEI score for the three-day menu cycle was 91.1 and 37.2 for the Mediterranean and Western diet, respectively. Preliminary results from three participants fed both diets for 6 days: All three participants consumed within 5% of the planned diet with the exception of one participant, who, during the Mediterranean diet cycle, consumed 64%. Mean HEI calculated for actual participant intake ( n  = 3, 6 days each) was: 89.7 Mediterranean, 36.4 Western Conclusions: The Mediterranean diet had a 10-fold higher ratio of omega-6: omega-3 fat than Western. A three-day menu cycle was planned and met goals for an anti-inflammatory feeding study. Recruitment is ongoing to study the feasibility of providing a Mediterranean style and Western style diet to adults with asthma in Baltimore City. Mean HEI for the first three recruits was similar to that of the planned menu, indicating that lack of strict diet adherence did not alter HEI goal of the diet. Although diet design was successful, there were challenges to feeding study participants that must be considered in future feeding studies. Adequate freezer space is key in food preparation and delivery. Acceptability of foods in the Mediterranean diet may effect diet compliance in those who typically eat a Western diet. Dietary restrictions and allergies excluded potential study subjects. Funding Sources: This publication was made possible by the Johns Hopkins Institute for Clinical and Translational Research (ICTR) which is funded in part by Grant Number UL1 TR001079 from the National Center for Advancing Translational Sciences (NCATS) a component of the National Institutes of Health (NIH), and NIH Roadmap for Medical Research. Its contents are solely the responsibility of the authors and do not necessarily represent the official view of the Johns Hopkins ICTR, NCATS or NIH. Supporting Tables, Images and/or Graphs: